Atrial fibrillation following electric shock requiring cardioversion - Paudel, Navaraj; Alurkar, V. M.; Kafle, Ramchandra; Sapkota, Subash (Nepalese Heart Journal, 2016)
Cardiac arrhythmias following electrical injury falls in a minority. Atrial arrhythmias including atrial fibrillation secondary to electrical shock are even more uncommon. This is a case report of AF requiring pharmacological cardioversion on a 41 year old female following an electrical shock. Initial attempt of electrical cardioversion had failed. Successful pharmacological cardioversion was achieved after 6 hours of amiodarone infusion (12-13 hours after the electric shock). Baseline electrocardiography showed normal pattern post cardioversion. Serum cardiac specific markers, electrolytes, thyroid function, chest x-ray and echocardiographic reports were all within normal limits.Nepalese Heart Journal 2016; 13(1): 31-34